FIDIC - A Guide for Practitioners - Jaeger, Axel-Volkmar. author. aut Link
XXXVI, 446 p. 41 illus., 20 illus. in color.
Keywords: In 1999, a suite of three new conditions of contract was published by FIDIC, following the basic structure and wording harmonised and updated around the previous FIDIC Design-Build and Turnkey Contract (the 1992 ‘‘Orange Book’’). These conditions, known as the ‘‘FIDIC rainbow, were the Conditions of C- tract for: l Construction, the so-called Red Book, for works designed by the Employer l Plant and Design-Build, the so-called Yellow Book, for works designed by the Contractor l EPC/Turnkey Projects, the so-called Silver Book, for works designed by the Contractor The ?rst is intended for construction works where the Employer is responsible for the design, as for per the previous so-called Red Book 4th Edition (1987), with an important role for the Engineer. The other two conditions of contract are intended for situations when the Contractor is responsible for the design. The Plant and Design-Build Contract has the traditional Engineer while the EPC/Turnkey Contract has a two-party arran- ment, generally with an Employer’s Representative as one of the parties.